2007
DOI: 10.1007/s00520-007-0302-3
|View full text |Cite
|
Sign up to set email alerts
|

The palliative prognostic score and survival in patients with advanced solid tumors receiving chemotherapy

Abstract: The PaP score seems to discriminate patients who could benefit by palliative chemotherapy from those who could better benefit by supportive and palliative approach. However, the data are insufficient to validate the use of the PaP score in patients to be treated with palliative chemotherapy, and further trials should be planned to assess its ability to improve the quality of care in oncology and the appropriateness in the choice of palliative chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 42 publications
0
47
2
Order By: Relevance
“…Although the presence of multiple metastatic sites [16] and raised CRP level [17][18][19][20] were reported as valuable prognostic factors both in patients with advanced cancer and in palliative care patients, neither of these factors were prognostically significant in the present study, despite the short survival of the respective cohort. In addition, an association of decreased Alb level with poor prognosis was not demonstrated in this study, partly due to the comparatively well-maintained Alb level (median value of 3.5 g/ dl) in our patients, though this association has been identified in the literature [3,6,13,16,19]. Even when the cutoff value of Alb was set at 3.0 g/dl or a prognostic nutritional index [PNI; 10 9 Alb (g/dl) ?…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Although the presence of multiple metastatic sites [16] and raised CRP level [17][18][19][20] were reported as valuable prognostic factors both in patients with advanced cancer and in palliative care patients, neither of these factors were prognostically significant in the present study, despite the short survival of the respective cohort. In addition, an association of decreased Alb level with poor prognosis was not demonstrated in this study, partly due to the comparatively well-maintained Alb level (median value of 3.5 g/ dl) in our patients, though this association has been identified in the literature [3,6,13,16,19]. Even when the cutoff value of Alb was set at 3.0 g/dl or a prognostic nutritional index [PNI; 10 9 Alb (g/dl) ?…”
Section: Discussioncontrasting
confidence: 60%
“…Several studies have been undertaken in order to establish palliative prognostic indices or scores in terminally ill cancer patients [12,13]. The survivals of terminally ill patients were found to be often overestimated by physicians in a large prospective cohort study [14], and against this background, we consider that prognostic factors are essential for planning optimal end-of-life treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the oncology seting, the validation studies were performed in Australia, Italy, and Japan [56][57][58][59]. Initially, a validation study of the oncology seting was reported by Glare et al in 2004, recruiting 100 patients receiving medical or radiation oncology care [56].…”
Section: Palliative Prognostic (Pap) Scorementioning
confidence: 99%
“…The external validity of these measures may also be questionable, because most were not derived or rigorously applied in an inpatient hospital setting with a diverse population of patients. 25,26 In fact, most of these studies were done on patients who were already determined to be terminally ill, making these tools less relevant for patients who are still receiving anticancer therapy. 22,[27][28][29] Tools such as the PaP and PPI were also developed at a time when the electronic medical record (EMR) could not be appropriately leveraged to aid in clinical decision-making.…”
Section: Introductionmentioning
confidence: 99%